The Black Economy in Southeast Asia: Current Issues and Future Challenges - Schaper, Michael (ISEAS – Yusof Ishak Institute, 2020)
EXECUTIVE SUMMARY • Between 1991 and 2015, the level of black economy activity in Southeast Asia equalled 33.4% of regional GDP, higher than for the rest of East Asia and above the global average. • By 2015, however, the regional average had declined to 28.3% of GDP. • The level of black economy activity remains highest in Myanmar and Thailand, and lowest in Singapore and Vietnam. • Whilst black economy activity has declined, several problem areas remain. Tax collection is still weak and poorly enforced in many parts of the region. Corruption is an ongoing issue, as is smuggling (especially of wildlife, timber, jade and gemstones) and illegal transfers of money out of China into Southeast Asia. • Emerging additional threats include the growth of the methamphetamine drug trade, and the likely prospect that Covid-19 will push many small formal businesses out of the regulated economy as they attempt to survive the current downturn. The financial cost of Covid-19 may also weaken the ability of nations to sufficiently fund enforcement activities in the near future. • Whilst ministerial and senior government fora already exist to co-ordinate ASEAN work in this area, much remains to be done. This includes a greater adoption of electronic banking and traceable online money transfers; greater usage of biometrics for identity authentication; improvements in tax collection rates in several jurisdictions; a sustained clampdown on smuggling; and regulation of cryptocurrencies to ensure they are not used as a black market tool.